The role of information technology governance in activating the internal control system - slimani, KHadidja (Journal of Excellence for Economics and Management Research, 2022)
This study aims to identify the various concepts related to governance, information technology, and the internal control system, and the nature of the relationship between them, and to study the level of application of the requirements of information technology governance in the banks under study, and its impact on the internal control system, through a survey study of a group of employees and frameworks of public banks. Algerian, and one of the results we reached in this study, that corporate governance is closely related to the structure of the internal control system and is a stage of its development, the governance of information technology in banks is applied and rises to the required level, the governance of information technology has a positive impact on the internal control system